2008
DOI: 10.1042/cs20070193
|View full text |Cite|
|
Sign up to set email alerts
|

Normal-sodium diet compared with low-sodium diet in compensated congestive heart failure: is sodium an old enemy or a new friend?

Abstract: The aim of the present study was to evaluate the effects of a normal-sodium (120 mmol sodium) diet compared with a low-sodium diet (80 mmol sodium) on readmissions for CHF (congestive heart failure) during 180 days of follow-up in compensated patients with CHF. A total of 232 compensated CHF patients (88 female and 144 male; New York Heart Association class II-IV; 55-83 years of age, ejection fraction <35% and serum creatinine <2 mg/dl) were randomized into two groups: group 1 contained 118 patients (45 female… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
141
3
20

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 203 publications
(168 citation statements)
references
References 46 publications
4
141
3
20
Order By: Relevance
“…In addition, there was a high proportion (33.9%) of exclusions, mainly due to inadequate urine collections. In the Cochrane meta-analysis of the randomized trials, 14 one of these trials in heart failure 17 should not have been included because the participants were severely salt-and water-depleted due to aggressive diuretics therapy (furosemide 250-500 mg twice daily). The optimal salt intake is not clear, at present, but there is no doubt that salt reduction is mandatory in any country in which salt consumption is extremely high, such as Japan.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there was a high proportion (33.9%) of exclusions, mainly due to inadequate urine collections. In the Cochrane meta-analysis of the randomized trials, 14 one of these trials in heart failure 17 should not have been included because the participants were severely salt-and water-depleted due to aggressive diuretics therapy (furosemide 250-500 mg twice daily). The optimal salt intake is not clear, at present, but there is no doubt that salt reduction is mandatory in any country in which salt consumption is extremely high, such as Japan.…”
Section: Discussionmentioning
confidence: 99%
“…26) Studies have indicated that the normal intake of salt can not only maintain the normal operation of the cells and organs of the body in patients with heart failure, but at the same time will also minimize the damage to the internal environment for long-term use of diuretics, and then increase the survival of patients with heart failure and improve their quality of life. 1) The age range of the heart failure patients enrolled in this study was 60 to 89 years old. As age increases, metabolism gradually becomes slower.…”
Section: Discussionmentioning
confidence: 99%
“…1) But so far, the treatment of heart failure is still in the stage of the invention of cardiotonics and diuretics. Diuretics, particularly potent loop diuretics, have long been accepted as the first-line treatment for patients with severe CHF and extreme fluid retention.…”
mentioning
confidence: 99%
“…However, the randomized study [44] comparing low-sodium and normal-sodium diets followed by patients taking high doses of furosemide, revealed that those who limited sodium intake were more often hospitalized. It was associated with changes in the renin-angiotensin-aldosterone (RAA) system, occurring while being on a low-sodium diet.…”
Section: Adherencementioning
confidence: 99%